Differentially Accumulated Proteins in Coffea arabica Seeds during Perisperm Tissue Development and Their Relationship to Coffee Grain Size - Alves, Leonardo Cardoso; Magalhães, Diogo Maciel De; Labate, Moînica Teresa Veneziano; Guidetti-Gonzalez, Simone; Labate, Carlos Alberto; Domingues, Douglas Silva [UNESP]; Sera, Tumoru; Vieira, Luiz Gonzaga Esteves; Pereira, Luiz Filipe Protasio (American Chemical Society (ACS), 2016)
Coffee is one of the most important crops for developing countries. Coffee classification for trading is related to several factors, including grain size. Larger grains have higher market value then smaller ones. Coffee grain size is determined by the development of the perisperm, a transient tissue with a higly active metabolism, which is replaced by the endosperm during seed development. In this study, a proteomics approach was used to identify differentially accumulated proteins during perisperm development in two genotypes with regular (IPR59) and large grain sizes (IPR59-Graudo) in three developmental stages. Twenty-four spots were identified by MALDI-TOF/TOF-MS, corresponding to 15 proteins. We grouped them into categories as follows: storage (11S), methionine metabolism, cell division and elongation, metabolic processes (mainly redox), and energy. Our data enabled us to show that perisperm metabolism in IPR59 occurs at a higher rate than in IPR59-Graudo, which is supported by the accumulation of energy and detoxification-related proteins. We hypothesized that grain and fruit size divergences between the two coffee genotypes may be due to the comparatively earlier triggering of seed development processes in IPR59. We also demonstrated for the first time that the 11S protein is accumulated in the coffee perisperm.
Keywords: grain size; perisperm metabolism; proteomics; quality; seed development